ALLOCATION AND ATTITUDES. - Jacobsen, Lyle E. (The Accounting Review, 1962)
The author believes that accounting justifications which are claimed to be theory differ from each other principally because of differences in individual attitudes or philosophies which, in turn, are an inseparable part of individual personalities. The process of attitude formation should be left to sociologists, psychologists and others. In the accounting fraternity, however, one might attempt to trace the effect of defined attitudes upon conceptual formulations. It is doubtful, for example, that a satisfactory explanation has been offered regarding exactly why straight line depreciation, first in first out, original cost for fixed assets, and even matching are so appealing. Some insight into the influence of attitudes upon accounting theory might be gained from a study of various "schools of economic thought." The influence of economic thought upon accounting theory may be stronger than one now realize. In accounting theory and practice, it has been discovered that accountants possessing presumably identical amounts of knowledge about a problem and comparable analytic skills still may differ on matters of reporting and of theory.